P067 Proliferating intestinal macrophage populations in human inflammatory bowel disease. (16th January 2018) - McDonald, E; Wright, P; Bain, C; Bravo-Blas, A; Robertson, E; Mowat, A; Milling, S; Gaya, D
Abstract: Background: The role of the immune system within the gastrointestinal tract is to maintain intestinal homeostasis by meticulously protecting the host from the invasion of harmful pathogens, whilst remaining unresponsive to the commensal microbiota. Cells of the mononuclear phagocyte (MNP) lineage: monocytes, macrophages, and dendritic cells (DCs), are critical for this process. Despite their importance, differential identification of the various MNP populations has been challenging because of the significant overlaps in their surface marker expression. Studies of MNP ontogeny in mice have revealed that intestinal macrophages are derived from circulating monocytes, but this has not been thoroughly investigated in humans. We therefore aimed to accurately identify human intestinal MNPs, and to ascertain their functions in patients with inflammatory bowel disease (IBD). Methods: We developed 12-parameter flow cytometry protocols to identify and characterise human intestinal MNPs in colonic biopsies from patients with Crohn's disease (CD), ulcerative colitis (UC), or non-inflamed controls. Results: Firstly, we unambiguously distinguished between macrophages and dendritic cells in human intestinal lamina propria as CD45+ CD64- HLA-DR+ CD11c+ and CD45+CD64+ HLA-DR+, respectively. Secondly, we identify two distinct subsets within the macrophage population on the basis of their expression of the mannose receptor, CD206. Further examination of these macrophage sub-populations showed striking differences in their phenotypic characteristics. CD206+ macrophages expressed markers consistent with a mature macrophage phenotype, including high levels of CD68 and CD163, and lower expression of Trem1. The CD64+ HLA-DR- CD206- cells appear more similar to the semi-mature cells found in mice as intermediaries in the development of mature intestinal macrophages from monocytes. Finally, to address the contribution of the CD206+ and CD206- macrophages to intestinal inflammation we assessed their frequency and functions in CD and UC patients, both with active inflammation and during remission. There were no differences in proliferation under these conditions. Surprisingly however, a substantial proportion of both these subsets were proliferating, in contrast to what has been found in mice. Conclusions: We have successfully identified and purified MNP populations from human intestinal lamina propria utilising fresh colonic biopsies. Thorough characterisation reveals that human colonic macrophages appear to be derived from a monocytic precursor but, unlike murine intestinal macrophages, those in humans are highly proliferative. Targeting these proliferating cells may well represent a fruitful avenue to abrogate the chronic inflammation in IBD.